THE EVALUATION OF THE BACHELOR DEGREE PROGRAM IN DEVELOPED, RURAL, AND UNDEVELOPED AREAS IN UNIVERSITAS NEGERI JAKARTA - PRASETYONO, HENDRO (Jurnal Ilmiah Educational Management, 2016)
This research was aimed to evaluating the degree program educates in leading regions, outermost and underdeveloped country at the University of Jakarta. This study uses CIPPO evaluation consisting of components Context, Input, Process, Product and Outcomes. This research using kuantitative methodology and data analysis technique used is descriptive by analyzing the data within each component method CIPPO collected from interviews, observations, questionnaires, study documents and photographs. Results of the study: (1) Background policy, objectives and targets of the program SM-3T whole aspect has demonstrated the Jakarta State University to meet the standards as LPTK organizers SM-3T; (2) The work program, qualified instructors and staff education and infrastructure have been met, while for the financing aspects LPTKs not meet the standards as program organizers SM-3T; (3) The implementation of preconditions in the field, and the implementation of programs in the field in accordance with the provisions of the guidelines of the program SM-3T while the program management of the sub-aspect cooperation with the other parties have not been successful; (4) Competence of graduates of the program and mark the graduation program have been met in full; (5) The impact is felt by participants of the program gives a lot of positive things but not give certainty about the fate of the program participants who have passed.